Penerapan Strategi Public Relation pada Bank Jatim Cabang Utama Surabaya untuk Meningkatkan Citra Perusahaan - Farikha Rachmawati; Nadjandra Alya Jasmin; Septia Rahmatul Jannah (Institut Nalanda, 2024)
Bank Jatim is a region bank in Jawa Timur province. Bank Jatim has this division called Corporate Secretary that subdue Secretariat and Protocol division, Corporate Communication subdivision, and Investation Management subdivision. Public Relation itself are included in Corporate Communication subdivision. As a member of Corporate Communication subdivision, Public Relations Bank Jatim had important role to preserve corporate image. Bank Jatim used corporate public relations strategy.